Oversighting the regulatory agencies: from the regime of bureaucratic barriers to judicial review - Gamarra Abarca, Sebastian (2025)
Within the framework of administrative claims, the article analyzes the interactions between the resolution bodies of Indecopi (Commission for the Elimination of Bureaucratic Barriers and the Specialized Chamber for the Elimination of Bureaucratic Barriers) and the regulatory agencies, in order to identify the main limitations of the administrative jurisdiction, which come, among others, from the provisions of Legislative Decree 1256 and the jurisprudence of Indecopi.This situation generates control gaps that, in turn, result in the lack of protection of the citizens. To better illustrate this scenario, a historical overview of the Peruvian institutions involved is carried out, leading to a detailed review of the applicable regulations and jurisprudence. Finally, it concludes with the proposal of possible alternatives for improvement, emphasizing the revitalization of the Judicial Branch possible alternatives for improvement.